Gro Health digital app facilitates weight loss and reduces disease activity in psoriatic arthritis - Tim Blake; Nicola J. Gullick; Deepak Nagra; Charles E. Hutchinson; Thomas M. Barber (BMC Rheumatology, 2026)
Abstract Background Obesity is common in psoriatic arthritis (PsA) and is associated with higher disease activity, poorer treatment response, and increased cardiometabolic risk. Digital lifestyle interventions may offer significant support for weight management, but their role in PsA care remains insufficiently explored. Objective To evaluate the impact of a PsA-tailored version of the Gro Health app and digital tier 2 weight management program on patient body weight and disease activity. A secondary objective was to assess patient engagement with this platform as part of a service innovation in routine rheumatology care. Methods This longitudinal observational study recruited 200 adults with PsA and BMI ≥ 25 kg/m² from routine NHS rheumatology clinics at University Hospitals Coventry and Warwickshire NHS Trust, UK. Of these, 100 patients were offered access to the Gro Health app alongside usual care, and 100 were BMI-matched controls receiving standard care alone. Patients were followed for six months. App engagement, body weight, Composite Psoriatic Disease Activity Index (CPDAI), domain-specific disease activity, and patient-reported outcomes were analyzed. Outcomes were compared between app engagers, non-engagers, and BMI-matched controls. Results Forty-six patients engaged with the app at least weekly. App engagers achieved significantly greater weight loss compared with non-engagers and controls (− 1.55 kg vs. − 0.18 kg vs. + 1.7 kg; p < 0.001). CPDAI improved in engagers (− 0.58) but worsened in non-engagers and controls ( p < 0.001). Improvements were most pronounced in arthritis ( p = 0.017) and enthesitis ( p = 0.034) domains. Weight loss correlated significantly with improvements in disease activity (ρ = 0.372, p < 0.001). In multivariable analysis, changes in body weight and baseline disease activity remained independent predictors of CPDAI. Conclusions A multidimensional lifestyle app incorporating tier 2 weight management content, health coaching, and structured digital guidance was associated with modest weight loss and improvements in PsA disease activity, particularly in the arthritis and enthesitis domains. These findings support integrating coached digital weight management strategies into PsA care; however, larger controlled studies are required to confirm efficacy and optimize patient engagement.